PROGRAM ASSERTIVENES TRAINING DAN PROGRAM PSIKO EDUKASI KELUARGA SEBAGAI MODEL DALAM PREVENSI ADIKSI GAME ONLINE PADA REMAJA DI KOTA PADANG - Renidayati .; Suhaimi . (Jurnal Sehat Mandiri, 2018)
Excessive use of online games in adolescents can lead to addiction. Online game addiction is associated with limited time of rest, insomnia, sleep deprivation, academic decline, decreased self-esteem, and decreased life satisfaction with everyday life. Through Assertive Training Program and Psycho-educational Program in Families are expected to improve the ability of self-esteem, assertiveness and knowledge of teenagers to prevent the Online Game Addiction. The study design "Quasi-experimental pre-post test without control group" with an intervention of assertive Training Program and Psycho-Educational Program in Family. The results showed a difference of average in self-esteem, assertive behavior and knowledge of Online Games in the intervention group were given assertiveness training program and Psycho-educational program before and after the intervention with P value of 0.000 (p <0.05). Expected that exercise of assertive program and Psycho-Educational Program in Families can be used as a model in the prevention of online game addiction in adolescents, for nurses, counseling teachers in schools, and in communities